2011
DOI: 10.5251/abjna.2011.2.5.867.871
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and agricultural productivity enhancement in Nigeria: application of processed Moringa oleifera seeds for improved organic farming

Abstract: A mini field trial on the use and bio-decomposition of moringa oleifera seed cake as organic fertilzer was carried out in the Sheda Science and Technology Complex. The field investigation established the fact that organic farming based on the use of processed Moringa Oleifera seed as fertilizer on a maize farm achieved significant improvement on soil nutrients as shown in the plant yield as compared to the control. This integrated biodiversity management approach to agriculture will afford the farmers in devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 3 publications
2
11
0
2
Order By: Relevance
“…Organic farming based on using MMS as fertilizer on a maize farm achieved significant improvement on available nutrients in soil and increased the yield of maize. Emmanuel et al (2011) found that MMS has great support for available nutrients, microbial growth, yield and certain nutrient i.e., Mn, Cu, K and Ca compared to control plot. Davis et al (2006) stated that addition of MOR as a green manure significantly improved soil fertility and plant growh.…”
Section: Introductionmentioning
confidence: 92%
“…Organic farming based on using MMS as fertilizer on a maize farm achieved significant improvement on available nutrients in soil and increased the yield of maize. Emmanuel et al (2011) found that MMS has great support for available nutrients, microbial growth, yield and certain nutrient i.e., Mn, Cu, K and Ca compared to control plot. Davis et al (2006) stated that addition of MOR as a green manure significantly improved soil fertility and plant growh.…”
Section: Introductionmentioning
confidence: 92%
“…Indeed, Moringa oil could be a good substitute for olive oil in the diet as well as for non-food applications, like biodiesel, cosmetics, and a lubricant for fine machinery. Moreover, after oil extraction, the seed cake can be used in waste water treatment as a natural coagulant [4] or as an organic fertilizer to improve agricultural productivity [5]. …”
Section: Introductionmentioning
confidence: 99%
“…However, some people may fail to take up Moringa for household use or primary health care options it will still boost productivity and production. Intercrops of Moringa have led to a realization of high yields in horticultural crops and its organic fertilizer has been found to be more efficient in plant growth enhancement than organic matter from other plant compost (Prat et al, 2002;Emmanuel et al, 2011) and it is a biocide.…”
Section: Increased Livelihood Security and Diversificationmentioning
confidence: 99%